Survival of newly founded businesses: a log-logistic model approach - Talat Mahmood (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1997)
Based on a longitudinal data base we test the liability of adolescence hypothesis which states that new firm hazard rates follow an inverted U-shaped pattern. That is, the hazard rate is low for the initial period; the end of adolescence is marked by a hazard maximum, from which then rate declines monotonically. We use a log-logistic model which shows that the liability of adolescence“ argument describes the hazard rates of new establishments for all two and three-digit industries fairly well. Further, the rate shows that the desegregation of industries matters, and considerable differences are found within and across two and three-digit low-, moderate- and high-tech industries. In assessing the effect of market environment conditions on risk we find that risk tends to be elevated in a relatively large number of two-digit low- and high-tech industries in the presence of scale economies, but it is substantially reduced in moderate-tech industries. By contrast, the hazard rate tends to be reduced for quite a large number of three-digit low-, moderate- and high-tech industries in comparison with the two-digit industries, indicating a longer adolescence. The influence of start-up size in reducing the hazard rate is apparently similar between two and three digit low-, moderate- and high-tech industries. The impact of market growth on the risk of failure is not much different for both two and three-digit low-, moderate- and high-tech industries. That is, market growth tends not to reduce the risk exposure. R&D intensity exerts influence interchangeably on the risk of failure confronting new establishments within the two and three-digit low-, moderate- and high-tech industries. – – Basierend auf Längsschnittdaten testen wir die Hypothese der ,,Liability of Adolescene“. Diese besagt, daß die Risikorate einem umgekehrten U-förmigen Verlauf folgt. Das bedeutet, daß die Risikorate in der Anfangsphase niedrig ist; das Ende der ,,Adolescence“ durch ein Maximum der Risikorate bestimmt wird, welche danach monoton abfällt. Das log-logistische Modell stellt die Ergebnisse für alle zwei- und dreistelligen Industrien am besten dar. Ferner zeigen die Ergebnisse, daß das Niveau der Aggregation eine große Rolle spielt und bemerkenswerte Unterschiede zwischen und innerhalb zweistelliger und dreistelliger low-, moderate- und high-tech Industrien zu finden sind. Bei der Einschätzung des Effekts von Charakteristiken der Marktumgebung auf das Risiko finden wir, daß das Risiko dazu tendiert, in einer relativ großen Anzahl von zweistelligen low- und high-tech Industrien erhöht zu werden, wenn Skalenerträge vorliegen, sich jedoch substantiell in moderate-tech Industrien verringert. Im Gegensatz dazu tendiert die Hazard Rate zu einer Verringerung für eine recht große Zahl von dreistelligen low-, moderate- und higt-tech Industrien im Vergleich mit zweistelligen Industrien, was auf eine längere ,,Adolescence“ hindeutet. Der Einfluß der Anfangsgröße auf die Verringerung der Hazard Rate ist offensichtlich ähnlich in zwei- und dreistelligen low-, moderate- und high-tech Industrien. Der Einfluß des Marktwachstums auf das Risiko ist nicht zu unterschiedlich für zwei- und dreistellige Industrien. Das bedeutet, Marktwachstum tendiert nicht zu einer Verringerung des Risikos. Die FuE-Intensität übt einen Einfluß auf das Risiko sowohl in zwei- und dreistelligen low-, moderate- und hightech Industrien durch Neugründungen aus.
Keywords: 330